2021
DOI: 10.1155/2021/5551637
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Etiology of Elephantiasis and Its Associated Risk Factors in Jeldu District, West Shoa, Ethiopia

Abstract: Elephantiasis is the main cause of tropical lymphoedema in Ethiopia. The aim of the current study was to assess the etiology of elephantiasis and its associated risk factors. Cross-sectional community-based study was carried out from March to May 2020 in seven purposively selected villages of Jeldu district. Identified suspected cases of elephantiasis in those villages were interviewed, clinically observed, and serologically examined using filariasis test strip kits at their respective houses during day time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In the present study majority of patients were in the early stage of podoconiosis (Stage I and Stage II). This agreed with a study conducted in Dana district and Jeldu district west shoea, Ethiopia [25, 32]. Since most cases of podoconiosis in present study were in early stage of disease, secondary prevention is potentially helps to control the diseases progression.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study majority of patients were in the early stage of podoconiosis (Stage I and Stage II). This agreed with a study conducted in Dana district and Jeldu district west shoea, Ethiopia [25, 32]. Since most cases of podoconiosis in present study were in early stage of disease, secondary prevention is potentially helps to control the diseases progression.…”
Section: Discussionsupporting
confidence: 91%
“…Lymphatic filariasis is a tropical disease caused by parasitic nematode infection. This investigation revealed that eight out of 14 studies identified Wucheria bancrofti as the causative agent for lymphatic filariasis (12, [16][17][18][19][20][21][22], while the remaining six articles did not specify the species of agent. Each study had a different method of parasite identification, some used patient blood examination, while others preferred molecular analysis of PCR techniques or examined the mosquitoes under a microscope (18,(22)(23).…”
Section: Agent Of Lymphatic Filariasismentioning
confidence: 99%